Efficacy and safety of celecoxib in the treatment of acute pain due to ankle sprain in a latin american and middle eastern population - Cárdenas Estrada, Eloy; Oliveira, Lindomar Guimarães; Abad, Hernán Leonardo; Elayan, F.; Khalifa, N.; El-Husseini, Timour (2009)
Ankle sprains are common acute softtissue injuries. This 7-day open-label, multicentre, randomized study compared the efficacy and safety of celecoxib with non-selective non-steroidal antiinflammatory drugs (NSAIDs) in treating acute ankle sprain with moderate-tosevere ankle pain in 278 patients. Patients received either celecoxib (400 mg loading dose followed by 200 mg twice daily) or standard doses of non-selective NSAIDs. The primary endpoint was a change in the patient’s assessment of ankle pain on a 0 mm (no pain) – 100 mm (worst possible pain) visual analogue scale (VAS) at day 3 compared with baseline. From a baseline of 73 mm, mean VAS pain scores decreased to 29 and 32 mm in the celecoxib and non-selective NSAID groups, respectively. The lower limit of the 95% confidence interval for the treatment difference with regard to change from baseline was greater than the preestablished non-inferiority margin of –10 mm. Using an initial loading dose, celecoxib was at least as efficacious as non-selective NSAIDs in treating acute pain due to ankle sprain